2013
DOI: 10.3390/cryst3010257
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Graphene—Metal Contact

Abstract: Abstract:The contact resistance between graphene and metal electrodes is crucial for the achievement of high-performance graphene devices. In this study, we review our recent study on the graphene-metal contact characteristics from the following viewpoints: (1) metal preparation method; (2) asymmetric conductance; (3) annealing effect; (4) interfaces impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 81 publications
(109 reference statements)
7
43
0
Order By: Relevance
“…After metal sputtering, the appearance of few spectral features in the spectral range below 1500 cm -1 (in the range of 1300-1400 cm -1 ) and at the same time an increase in the band width of G-band can be attributed to the introduction of defects sites due to the sputtering. Liu et al observed similar behavior, when the researchers deposited Aluminum (Al) by means of sputtering technique [36]. It is plausible that silver atoms, in our case, during the sputtering process retain high kinetic energy, transferred to the graphene sheet.…”
Section: Resultssupporting
confidence: 53%
“…After metal sputtering, the appearance of few spectral features in the spectral range below 1500 cm -1 (in the range of 1300-1400 cm -1 ) and at the same time an increase in the band width of G-band can be attributed to the introduction of defects sites due to the sputtering. Liu et al observed similar behavior, when the researchers deposited Aluminum (Al) by means of sputtering technique [36]. It is plausible that silver atoms, in our case, during the sputtering process retain high kinetic energy, transferred to the graphene sheet.…”
Section: Resultssupporting
confidence: 53%
“…We find that gently [5][6][7][8][9]. We distinguish the role of air adsorbates and process residues on the doping of the graphene channel from that of the supporting SiO2 and argue that strain of graphene under the contacts plays an important role in increasing the contact resistance.…”
Section: Introductionmentioning
confidence: 95%
“…This work function value is similar to both silver (4.4 eV) and eGaIn (4.1-4.2 eV), and is therefore promising for achieving low interfacial resistance, which is a key property for many applications. [36][37][38] The contact resistance for the graphene-eGaIn junction is measured by the transmission line method, shown in Figure 3a. [39] This method is also used to measure contact resistance for different material sets, as shown in Figure 3b and Figure S10 (Supporting Information).…”
mentioning
confidence: 99%